PELATIHAN KOMUNIKASI EFEKTIF DAN ETIKA KOMUNIKASI UNTUK MENINGKATKAN KESIAPAN KERJA SISWA SMK WIJAYA KUSUMA SURAKARTA - Andri Astuti Itasari; Dewi Maria Herawati (LPPM Institut Pendidikan Nusantara Global, 2026)
The readiness of vocational high school (SMK) students to enter the workforce is not only determined by technical skills but is also strongly influenced by soft skills, particularly effective communication and communication ethics. Based on the identified needs at SMK Wijaya Kusuma Surakarta, it was found that most students had not yet developed optimal communication skills, either in expressing ideas or interacting professionally. This community service program aimed to improve students’ effective communication abilities and their understanding of ethical communication as preparation for entering the professional world. The implementation methods included socialization sessions, training in oral and written communication techniques, and mentoring in creating curriculum vitae and conducting job interview simulations. The results of the program showed significant improvements in students’ communication abilities, indicated by the increase in the ability to express opinions clearly from 41% to 82%, the use of polite and effective language from 47% to 88%, the ability to prepare professional curriculum vitae from 33% to 79%, self-confidence during interview simulations from 38% to 85%, and understanding of communication ethics from 52% to 90%. Students were also able to prepare curriculum vitae that met workplace standards and demonstrated greater confidence in professional interactions. This program had a positive impact on strengthening vocational students’ readiness to face professional challenges and fostering awareness of the importance of ethical communication as a fundamental asset in building healthy and productive workplace relationships.